(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to (1). know the procedure for optimizing waste management in the Final Processing Site (TPA) area using the Sanitary Landfill system and the Landfill Control System in Bengkala Village, Buleleng Regency. (2). To find out the strategy for fulfilling and managing Bengkala landfill facilities and infrastructure. This type of research in this study uses case studies. Approach This research is a type of qualitative research. The location of this research is the Bengkala TPA, Bengkala Village, Kubudindingan District, Buleleng Regency. The methods used in this study are interviews, observation and documentation. Data analysis techniques used in this study are data reduction, data display, and conclusion. The results of this study are that revitalization or procedures for optimizing waste management at the Bengkala landfill can be carried out by means of planning carried out at the bengkala landfill, namely using 5 blocks (2). Using the landfill method at the Bengkala landfill, namely the trench or ditch method and the area method (3). Coating With Geotextiles. (4). Installing Leachate Pipes. (5). Perform Gas Release Pipe Installation. (6) perform Base Coating. (7). implemented a Sanitary Landfill at the Bengkala Landfill in collaboration with the Buleleng Regency Government and the Ministry of Energy and Mineral Resources utilizing waste as an alternative material for electrical energy. The strategy carried out by the Buleleng Regency Environmental Service for the fulfillment and management of Bengkala TPA facilities and infrastructure is the budgeting, planning, implementation and evaluation stages.